Visual Brand Architecture WB Kitchen - Dzaky Assrof; San Ahdi (Lembaga Pengembangan Kinerja Dosen, 2024)
WB Kitchen is a culinary business located in Batusangkar, West Sumatra. WB Kitchen has 3 subsidiaries, namely WB Cake, WB Rendang, and WB Catering.WB itself is taken from the initials of Mrs. Rahmiwati Bur's nickname, namely